Phase II study of TP300 in patients with advanced gastric or gastro-oesophageal junction adenocarcinoma. Issue 1 (December 2016) - Propper, David; Jones, Keith; Anthoney, D.; Mansoor, Wasat; Ford, Daniel; Eatock, Martin; Agarwal, Roshan; Inatani, Michiyasu; Saito, Tomohisa; Abe, Masaichi; Evans, T.
Abstract Background TP300, a recently developed synthetic camptothecin analogue, is a highly selective topoisomerase I inhibitor. A phase I study showed good safety and tolerability. As camptothecins have proven active in oesophago-gastric adenocarcinomas, in this phase II study we assessed the efficacy and safety of TP300 in patients with gastric or gastro-oesophageal junction (GOJ) adenocarcinomas. Methods Eligible patients had metastatic or locally advanced gastric or Siewert Types II or III GOJ inoperable adenocarcinoma. Patients were chemotherapy naïve unless this had been administered in the perioperative setting. TP300 was administered as a 1-h intravenous infusion every 3 weeks (a cycle) for up to 6 cycles at a starting dose of 8 mg/m2 with intra-patient escalation to 10 mg/m2 from cycle 2 in the absence of dose-limiting toxicity. Tumour responses (RECIST 1.1) were assessed every 6 weeks. Toxicity was recorded by NCI-CTCAE version 3.0. Using a modified two-stage Simon design (Stage I and II), a total of 43 patients were to be included providing there were 3 of 18 patients with objective response in Stage I of the study. Results In Stage I of the study 20 patients (14 males, 6 females), median age 67 years (range 40 − 82), performance status ECOG 0/1, with GC [14] or GOJ carcinoma [6] were enrolled. Of the 16 evaluable patients, 11 received the planned dose increase to 10 mg/m2 at cycle 2, 2 decreased to 6 mg/m2, and 3 continued on 8 mg/m2 . There were no objective responses after 2 cycles of treatment. Twelve patients had stable disease for 1 − 5 months and 4 had progressive disease. Median progression free survival (PFS) was 4.1 months (CI [1.6 − 4.9]), median time to progression (TTP) was 2.9 months (CI [1.4 − 4.2]). Grade 3/4 toxicities (worst grade all cycles) included 7 patients (35 %) with neutropenia, 4 patients (20 %) with anaemia, 2 patients (10 %) with thrombocytopenia, and 3 patients (15 %) with fatigue. This study was terminated at the end of Stage I due to a lack of the required (3/18) responders. Conclusions This study of TP300 showed good drug tolerability but it failed to demonstrate sufficient efficacy as measured by radiological response. Trial registration EU-CTR 2009-012097-12 2009-09-03